Дослідження технології 5G на платформи IoT - Сазонов, Б. О. (ХНУРЕ, 2024)
The article explores the potential of 5G technology in the context of the Internet of Things (IoT). It examines the impact of high-speed, low-latency and low-power (HL-LP) 5G communication on the development of smart systems in the home environment. The use of 5G in Broad Band - IoT (BB-IoT) tssechnology’s opens up new perspectives for expanding the functionality and efficiency of intelligent systems. The article examines the benefits and challenges of implementing 5G in smart homes, such as high bandwidth, low latency, improved scalability, and network security
Keywords: технології 5G; платформа IoT